The Role of School Culture in Holistic Education Development in Muhammadiyah Elementary School Sleman Yogyakarta - Widodo, Hendro (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This research aims to: 1) describing the cultural approach in the development of holistic education in Muhammadiyah Elementary School: 2) finding the role of school’s stakeholders in realizing holistic education in Muhammadiyah Sleman Elementary School. This research was conducted at Muhammadiyah Sleman Elementary School Yogyakarta. This research was qualitative research of phenomenology by interpretive paradigm. Data collection techniques were observation, interview, and documentation. Data analysis was by interactive model, which were data reduction, data display, and data conclusion drawing/verification. The results of this research are: 1) school culture becomes an important part in improving education quality. The development of holistic education in Muhammadiyah elementary school using cultural approach. Values, beliefs, and habits are built on the school community’s awareness and will, which is bottom-up in nature. The basis of realizing holistic education in school is the school culture. Positive school culture will make holistic education done well, on the contrary negative school culture will make holistic education difficult to obtained. Therefore schools should build strong school culture in implementing holistic education; 2) school stakeholders who very important in realizing holistic education at Muhammadiyah Sleman Elementary School are principal, guard team of school culture, teachers, families, school committees, community, and guard team of holistic education.